Studies of the content of optical isomers of amino acids in food - A. S. Knyazeva; D. A. Utyanov; A. V. Kulikovskii; A. A. Kurzova (Пищевые системы, 2021)
Food products undergo a wide range of chemical changes during their processing and storage. As a result of such reactions, both new chemical compounds and optical isomerization of compounds already present in the composition can be formed. The second case concerns the formation of D-enantiomers of amino acids from their L-forms. D-forms of amino acids not only have no biological value for the body, but also often have a negative effect on the human body due to the impossibility of metabolizing them and, as a consequence, their accumulation in the body. The aim of the work was to study the quantitative content of D-isomers of amino acids in milk that passed the ultra-pasteurization process and dairy products based on bacterial starter culture. The research results showed that in both cases of the considered technological methods, amino acid isomerization occurs. The highest degree of isomerization was observed in kefir samples relative to other samples. However, from the results obtained, it is not possible to estimate which amino acid is most susceptible to the racemization process, since different samples contained different D-isomers of amino acids. The smallest amount of D-isomers is found in milk that has not undergone any industrial processing. Studies have shown that technological processing of milk inevitably leads to the formation of D-isomers of amino acids, and this, in turn, at least reduces the nutritional and biological value of the product, which makes it necessary to conduct deeper studies in this direction to establish the most important factors in the process of racemization of amino acids in food products.